'What are you taking away with you?' Closing radio counselling encounters by reviewing progress. (June 2018) - Thell, Nataliya; Peräkylä, Anssi
Psychological radio counselling is a relatively recent development in psychological practice, where professionals provide psychological help via mass media communication. In the media context, a professional and a help-seeker face a number of communicative challenges, one of which is to close the encounter meaningfully with regard to its counselling and radio tasks. This study explicates how radio counselling encounters can be rounded off by summarising and reviewing the progress achieved in understanding the caller's problem. At the end of the encounters, the radio psychologist invited callers to look back at the conversation and to formulate possible gains from it. On one hand, the radio psychologist encouraged callers' reflection and acknowledged the callers' entitlement to pass judgement on the outcomes of the encounter. On the other hand, the radio psychologist checked and subsequently reviewed the caller's understanding of his or her problem and its solutions. We discuss how the practice was used to round off the encounters in a distinct way with an orientation to their counselling and radio objectives.